Residents' roles as environmental policy actors using an urban governance framework: A case study of a tree planting program. (April 2023) - Geron, N.A.; Martin, D.G.; Rogan, J.; Healy, M.
Abstract: Many North American cities are pursuing tree planting as part of their climate mitigation policies. Tree planting initiatives (TPI) are decentralized environmental programs since ongoing stewardship is dependent on the individuals who adopt and plant the trees. Therefore, the successful implementation of tree planting is subject to the vagaries of individual landowner actions and decision-making. There is a lack of research on the opportunities for environmental policy and governance that explicitly draws upon residents as policy actors. This paper uses a governance framework to examine TPI governance in two registers: first, how residents are incorporated into the governance network in each city, and second, resident perspectives and decision-making as policy actors. We find that decentralized environmental programs such as tree planting can encourage strong networks if they are founded on reliable partnerships and multiple ways of reaching individual residents. Residents are categorized into four different groups – policy actors, communicators, negotiators, and passive recipients – based on their actions, decision-making, and motivations. Residents categorized as policy actors, communicators and negotiators showcased increased community and tree care stewardship activities. Decentralized environmental governance can facilitate resident conceptualization as policy actors by encouraging individuals participation in program decision-making. Highlights: Residential tree planting programs can be successful in dense urban neighborhoods. Decentralized environmental governance relies heavily on residents to be policy actors. Residents that are policy actors perform both community and tree care stewardship. Environmental programs can encourage individuals by providing choices and incentives to communicate about the program.